2020
DOI: 10.13106/jafeb.2020.vol7.no2.89
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Risk Based Audit Approach in the Independent Audit Firms: A Study of Case of Vietnam

Abstract: This study was conducted to examine how independent audit firms in Vietnam understand and use risk based audit approach (RBAA) in audit practice. To answer the research questions, the researchers used primary and secondary data collected from 2018 to 2019. The results from the interview survey showed that audit firms were aware of the advantages of adopting RBAA. However, RBAA is practiced to a moderate extent by audit firms in Vietnam. Big 4 audit firms use RBAA more popularly than Non-Big 4 audit firms. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The findings indicated that the BRA implementation cost (H1) is an obstacle to the widespread use of the BRA methodology in the Yemeni context. This finding is consistent with those of Abdullatif and Al-Khadash 10 and Le and Nguyen, 44 who found that the high cost of audits based on BRA prevented the widespread application of this methodology in Jordan and Vietnam.…”
Section: Discussion Of Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The findings indicated that the BRA implementation cost (H1) is an obstacle to the widespread use of the BRA methodology in the Yemeni context. This finding is consistent with those of Abdullatif and Al-Khadash 10 and Le and Nguyen, 44 who found that the high cost of audits based on BRA prevented the widespread application of this methodology in Jordan and Vietnam.…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…The findings of this study are in line with those of previous research. 10,13,44 . However, the results contradicted those of some of the cited sources, specifically, Al-Nodel & Turley 45 and Essa 27 who found that the cost of audits did not prevent the BRA approach from being implemented in KSA or Libya.…”
Section: Conclusion Limitations and Recommendationsmentioning
confidence: 99%
“…Positive statistical significance was shown between risk-based audit planning and SACCOs' bottom lines. According to Le and Nguyen (2020), six variables affect RBAA adoption: auditor competence, technological progress, audit fees, auditor motivation, audit duration, and client risk. Of them, the competence of auditors and advances in technology have the greatest and most beneficial effects on RBAA's spread.…”
Section: Pearson Correlationmentioning
confidence: 99%
“…Professional knowledge includes professional skills, career skills, and knowledge of computers, which are important criteria of employees (Huang & Lin, 2011;Laker & Powell, 2011). Le and Nguyen (2020) used primary and secondary data collected from 2018 to 2019. The results from the interview survey showed that audit firms were aware of the advantages of adopting RBAA.…”
Section: Literature Reviewmentioning
confidence: 99%